(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2003)
An Eostyloceros antler fragment is described. The specimen makes part of the Montopoli (Lower Valdarno, Tuscany) collection preserved in the Geo-Paleontological section of the Natural History Museum of Florence. This site is the type locality of the homonymous Faunal Unit of the Italian Biochronological scheme; it includes the latest Early Villafranchian Mammal Age faunas. The occurrence of an Eostyloceros species among this material however, is in disagreement with the age of the Montopoli local fauna, which has been correlated with the Gauss-Matuyama boundary and thus dated to about 2.6 Ma. The youngest remains of this genus come from sites of eastern Europe Early Pliocene in age (Ruscinian Mammal Age). The possibility that the antler is an external element to the Montopoli assemblage is therefore contemplated.